2004
DOI: 10.1038/sj.npp.1300435
|View full text |Cite
|
Sign up to set email alerts
|

Methadone Maintenance Reduces Heroin- and Cocaine-Induced Relapse without Affecting Stress-Induced Relapse in a Rodent Model of Poly-Drug Use

Abstract: Although it is well established that methadone can be an effective treatment for opiate addiction, it is not clear how methadone maintenance affects cocaine use and cravings in individuals who self-administer both opiates and cocaine. In our attempt to explore the effect of methadone maintenance on the effects of cocaine, we first assessed the locomotor stimulatory effects of cocaine in rats maintained on methadone (0, 10, 20, or 30 mg/kg/day, via osmotic minipumps). Chronic methadone elevated baseline locomot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 76 publications
8
56
1
Order By: Relevance
“…In fact, during cocaine self-administration on a PR (Experiment 2), it was found that rats maintained on 30 mg/kg/day methadone failed to adjust to the increased work requirement to obtain drug infusions and, as a result, obtained significantly less cocaine than control animals. These results are consistent with previous findings from our laboratories showing that rats maintained on doses of methadone above 20 mg/kg/day do not respond for cocaine-conditioned cues, do not approach a cocaine-conditioned environment, and do not show reinstatement of cocaine seeking after priming injections of cocaine (Leri et al, 2004(Leri et al, , 2005(Leri et al, , 2006. It is important to note that methadone-induced blockade of cocaine seeking observed in our experiments is not an artifact of impaired sensory-motor functioning.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In fact, during cocaine self-administration on a PR (Experiment 2), it was found that rats maintained on 30 mg/kg/day methadone failed to adjust to the increased work requirement to obtain drug infusions and, as a result, obtained significantly less cocaine than control animals. These results are consistent with previous findings from our laboratories showing that rats maintained on doses of methadone above 20 mg/kg/day do not respond for cocaine-conditioned cues, do not approach a cocaine-conditioned environment, and do not show reinstatement of cocaine seeking after priming injections of cocaine (Leri et al, 2004(Leri et al, , 2005(Leri et al, , 2006. It is important to note that methadone-induced blockade of cocaine seeking observed in our experiments is not an artifact of impaired sensory-motor functioning.…”
Section: Discussionsupporting
confidence: 93%
“…It is important to note that methadone-induced blockade of cocaine seeking observed in our experiments is not an artifact of impaired sensory-motor functioning. In fact, rats tested in Experiment 2 displayed normal locomotor activity and those tested in our previous experiments showed no reduction of cocaine self-administration on a continuous schedule of reinforcement, and showed significant reinstatement of heroin and cocaine seeking after exposure to foot-shock stress (Leri et al, 2004(Leri et al, , 2006. Interestingly, it was found that methadone maintenance did not attenuate the rise in extracellular dopamine levels in the ventral striatum induced by acute cocaine injections.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In fact, it is well known that the effect of heroin primes on reinstatement is dependent on activation of muopioid receptor (MOP-r) (de Wit and Stewart, 1983;Shaham et al, 1996;Leri et al, 2004). In the paraventricular nucleus of the hypothalamus, AVP-producing parvocellular cells express MOP-rs, and activity of these cells is under tonic inhibition by endogenous opioids (Nikolarakis et al, 1987).…”
Section: Discussionmentioning
confidence: 99%